Immediate impact of a hurricane on the structure of a tropical butterfly community. (15th May 2018) - Mullany, Frances; Hollands, Georgina; Snaddon, Jake L.
Abstract: More intense and frequent hurricanes may lead to long‐lasting effects to tropical ecosystems. Here, we describe the immediate impact on the butterfly community of a lowland forest in Belize, following Hurricane Earl. Species richness and abundance increased posthurricane, likely driven by convergence of the organization between the canopy and understory communities.